Modeling the Mycobacterium tuberculosis Granuloma – the Critical Battlefield in Host Immunity and Disease - Guirado, Evelyn; Schlesinger, Larry (Frontiers in Immunology, 2013)
Granulomas are the hallmark of Mycobacterium tuberculosis (M.tb) infection and thus sit at the center of tuberculosis (TB) immunopathogenesis. TB can result from either early progression of a primary granuloma during the infection process or reactivation of an established granuloma in a latently infected person. Granulomas are compact, organized aggregates of immune cells consisting of blood-derived infected and uninfected macrophages, foamy macrophages, epithelioid cells (uniquely differentiated macrophages) and multinucleated giant cells (Langerhans cells) surrounded by a ring of lymphocytes. The granuloma’s main function is to localize and contain M.tb while concentrating the immune response to a limited area. However, complete eradication does not occur since M.tb has its own strategies to persist within the granuloma and to reactivate and escape under certain conditions. Thus M.tb-containing granulomas represent a unique battlefield for dictating both the host immune and bacterial response. The architecture, composition, function and maintenance of granulomas are key aspects to study since they are expected to have a profound influence on M.tb physiology in this niche. Granulomas are not only present in mycobacterial infections; they can be found in many other infectious and non-infectious diseases and play a crucial role in immunity and disease. Here we review the models currently available to study the granulomatous response to M.tb.